Higher Soluble ACE2 Levels and Increased Risk of Infection-Related Hospitalization in Patients on Maintenance Hemodialysis - Kawabe, Mayuko; Nakashima, Akio; Yamamoto, Izumi; Ohkido, Ichiro; Yokoo, Takashi; Urashima, Mitsuyoshi (Frontiers in Medicine, 2022)
Background: Angiotensin-converting enzyme 2 (ACE2) works as an endogenous counter-regulator of the renin-angiotensin system, which has pivotal roles in preventing both cardiovascular disease (CVD) and inflammation. In general populations, higher plasma soluble ACE2 levels were reported to be associated with increased risks of all-cause death and major CVD. Because infections are fatal in patients on maintenance hemodialysis, we aimed to explore whether soluble ACE2 levels are associated with an increased risk of infection-related hospitalization in these patients. Methods: Using data from a prospective, multicenter, cohort study conducted in Tokyo, Japan, we performed a post hoc analyses of 724 clinically stable patients on maintenance hemodialysis. We measured baseline serum soluble ACE2 levels and assessed potential determinants of its with infection-related hospitalization as a primary outcome as well as all-cause death and CVD as secondary outcomes using a Cox proportional hazards model. Results: The soluble ACE2 level (median, 0.16 ng/ml; interquartile range, 0.07 to 0.57 ng/ml) showed a weak negative association with age. During a median follow-up of 39 months, 106 patients (14.6%) were hospitalized with infectious diseases. Compared with the lower half of soluble ACE2 levels, the higher half was associated with an increased risk of infection-related hospitalization (hazard ratio, 1.57; 95% confidence interval, 1.02 to 2.41) with adjustment by other risk factors. On the other hand, there were no significant associations between soluble ACE2 and risks of all-cause death and CVD. Conclusion: Higher soluble ACE2 levels may associate with an increased risk of infection-related hospitalization in patients on maintenance hemodialysis.